Alcohol in Greenland 1950-2018: consumption, drinking patterns, and consequences. Issue 1 (1st January 2020) - Bjerregaard, Peter; Larsen, Christina V. L.; Sørensen, Ivalu K.; Tolstrup, Janne S.
ABSTRACT: Alcohol is the single most important public health challenge in Greenland. We provide an overview of alcohol consumption, drinking patterns, and consequences of excessive use of alcohol in Greenland since 1950 through a synthesis of published results and analyses of population-based interview surveys. The import of alcohol fluctuated over the last 70 years with a peak in the 1980s at 22 litres 100% alcohol per person per year. In 1950 and 2015, the import of alcohol was similar at 8 litres. Several explanations have been put forward to explain the changes including restrictions, increased tax, demographic changes, treatment of alcohol disorders, and public health interventions. The proportion of abstainers increased from 1993 to 2018 while the proportion of participants with regular consumption decreased. About half of the population reported binge drinking at least monthly. Compared with Denmark, there were more abstainers and binge drinkers in Greenland, and fewer had a regular consumption. Although genetics may play a role for drinking patterns, social and cultural conditions are more important. Exposure to domestic alcohol problems and sexual abuse in childhood parallel the recorded import of alcohol and is a likely cause of transgenerational consequences such as youth suicides and alcohol problems.